2017
DOI: 10.1007/s10853-017-0888-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glass-containing cranial implants: an overview

Abstract: Although metals have successfully been used as implants for decades, devices made out of metals do not meet all clinical requirements. For example, metal objects may interfere with some medical imaging systems (computer tomography, magnetic resonance imaging), while their stiffness also differs from natural bone and may cause stress-shielding and over-loading of bone. There has been a lot of development in the field of composite biomaterial research, which has focused to a large extent on biodegradable composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 83 publications
0
35
0
Order By: Relevance
“…BGs have a wide range of clinical applications for the reparation and reconstruction of bone, thus have been a preferential biomaterial for modification with Bi composites. 543,546,547 BGs have the ability to serve as an eluting agent of relevant therapeutics, contributing to therapeutic strategies against diseases such as osteomyelitis and bone cancer, 543,[548][549][550][551] particularly when combined with Bi as one the main components. Regarding the treatment of osteomyelitis, BGs by which the addition of Bi ions renders them with antimicrobial activity and promoted bone regeneration were investigated by Prasad et al 546 They demonstrated a combinatorial antibacterial effect and cell proliferation induction due to the combined action of antibacterial Bi 3+ ions and an increase in the pH value of the surrounding medium caused by the BG.…”
Section: Bi-based Biomaterials For Tissue Engineering and Implantationmentioning
confidence: 99%
“…BGs have a wide range of clinical applications for the reparation and reconstruction of bone, thus have been a preferential biomaterial for modification with Bi composites. 543,546,547 BGs have the ability to serve as an eluting agent of relevant therapeutics, contributing to therapeutic strategies against diseases such as osteomyelitis and bone cancer, 543,[548][549][550][551] particularly when combined with Bi as one the main components. Regarding the treatment of osteomyelitis, BGs by which the addition of Bi ions renders them with antimicrobial activity and promoted bone regeneration were investigated by Prasad et al 546 They demonstrated a combinatorial antibacterial effect and cell proliferation induction due to the combined action of antibacterial Bi 3+ ions and an increase in the pH value of the surrounding medium caused by the BG.…”
Section: Bi-based Biomaterials For Tissue Engineering and Implantationmentioning
confidence: 99%
“…Bioceramic materials constitute a vast group of inorganic and nonmetallic compositions with numerous applications in medicine and medical devices [71][72][73], of which orthopedic and dental implant use covers the major share [74][75][76]. Furthermore, with ceramic materials gaining increasing attention and sparking a discussion of their versatility and superiority over titanium-based implants [77], it is important to note that not all ceramic materials are suitable for implant purposes.…”
Section: Bioceramic Materialsmentioning
confidence: 99%
“…The other scientific areas in which Larry worked for many years and left important contributions, such as optical materials, electroceramics and nuclear waste encapsulation are well covered in the review of Larry Hench's legacy by Montazerian and Zanotto, the comprehensive review paper which opens the present special issue [2]. The special section includes three other review papers covering different scientific and technological aspects related to bioactive glasses, namely structure, properties and applications of phosphate glasses and fibers [3], dissolution of mesoporous silica in physiological environments [4] and applications of bioactive glasses in cranial implants [5]. Several papers deal with the investigation of novel compositions of silicate and phosphate bioactive glasses, in particular glasses with therapeutic ion delivery capability to enhance cellular response, an area highlighted in one of the most recent papers authored by Larry Hench in 2015 [6], which reflects the importance of this topic for applications of bioactive glasses in regenerative medicine and as antibacterial agent.…”
Section: ó Springer Science+businessmentioning
confidence: 99%